Challenging conceptualisations of work: Revisiting contemporary experiences of return to work and unemployment. Issue 1 (2nd January 2021) - Asaba, Eric; Aldrich, Rebecca M.; Gabrielsson, Hanna; Ekstam, Lisa; Farias, Lisette
ABSTRACT: This article draws on empirically derived illustrations of return to work and unemployment to critically explore how a narrow understanding of work pervades contemporary social policies and programmes. This is particularly relevant in economic and labour market transitions aligned with neoliberalism that individualise the social problem of unemployment and thus restrict occupational possibilities related to work. An overview of how work and related concepts have been conceptualised in occupational science scholarship is presented. After describing the theoretical orientation of the paper, three illustrations derived from a secondary analysis of data from projects conducted in Sweden and the United States are presented. The three empirically grounded illustrations are integrated with theory to highlight tensions between the politically informed structures that shape social policies and programmes and the individual experiences of work, unemployment, and return to work that users and providers of these programmes communicate. By asserting that success in work-related placement programmes is not synonymous with meaningful employment, we attempt to heighten awareness of the potential risks associated with a reliance on measuring work by merely being in paid formal employment.